PENGARUH GOOD CORPORATE GOVERNANCE (GCG) TERHADAP IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA INDUSTRI PERTAMBANGAN DAN PENGGALIAN (BUMN PERSERO TERBUKA) - PUTRI PAMUNGKAS, DIAN Putri (Jurnal Akuntansi AKUNESA, 2013)
This research aims to analyze the elements of Good Corporate Governance (GCG) ina company that may affect the implementation of social responsibility (CSR). Elementsexamined are the size of the Board of Commissioners, Board independence, institutionalownership, foreign ownership, and firm size as control variables. The population in thisresearch were all state-owned enterprises of mining and quarrying sectors listed on the StockExchange during the years 2007-2011. Analyses were performed by using content analysisand treated with test classic assumptions and hypothesis testing in multiple linear regression.From the results of this research showed that 10,7% of the implementation of corporate socialresponsibility is affected by the variables examined in this research.Key words: Corporate Social Responsibility (CSR), Corporate Governance (CG), firm size